KOMUNIKASI GURU TERHADAP ANAK ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD) DI SD MUHAMMADIYAH 2 TULANGAN SIDOARJO - Fildzah Aqmarina; Awang Dharmawan, S.I.Kom, M.A. (Universitas Negeri Surabaya, 2025)
This research aims to find out how interpersonal communication is carried out by teachers with Attention Deficit Hyperactivity Disorder (ADHD) children, such as the obstacles faced by teachers in the communication process with ADHD children and how to overcome these obstacles, especially at SD Muhammadiyah 2 Sidoarjo Reinforcement. The method used in this research is a qualitative descriptive method with a case study approach. The results of this research indicate that an inclusion teacher must be able to understand each ADHD student personally because they have different obstacles and needs. Generally, the obstacles experienced by ADHD students are not being able to control emotions, limited speaking ability, and disturbed focus. To create effective communication and overcome communication barriers that occur, teachers use various methods such as giving rewards if students do good things and giving consequences if students do not obey the rules. The teacher repeats words or instructions if they cannot receive the message conveyed to students. Teachers also guide students so that they can answer correctly, using verbal and nonverbal language. Keywords : Interpersonal Communication, Attention Deficit Hyperactivity Disorder (ADHD), Communication of Teacher and ADHD Student